5k + 7 + 3k can be simplified into 8k + 7
3k+16 = 5k subtract 3k from both sides 16 = 2k divide both sides by 2 8 = k
5k
The above expression can be simplified to:14n-2k
5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.
5k + 7 + 3k can be simplified into 8k + 7
To simplify the expression 5k + 7 + 3k, first combine like terms by adding the coefficients of the k terms: 5k + 3k = 8k. Then, add the constant term: 8k + 7 = 8k + 7. So, the simplified expression is 8k + 7.
The K stands for thousand. So 5k is 5,000 and 7 3K is either 73,000 or 7,000 and 3,000.
8k-7-3k=1? 5k-7=1 5k=8 k=8/5 8k-7 =-3k+1 11k-7=1 11k=8 k=8/11 8k-7-3k+1=0 5k-6=0 5k=6 k=6/5=1.2 depends on where = sign is in the question
3k+16 = 5k subtract 3k from both sides 16 = 2k divide both sides by 2 8 = k
5k
The above expression can be simplified to:14n-2k
5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.
It represents an algebraic equation in the variable, k.
(5k3 - 3k + 7) - (-2k3 + k2 - 9) = 7k3 - k2 - 3k + 16
It simplifies to 7k = 49 which gives k = 7.
==> 3k+14=k ==>3k-k=-14 ==>2k=-14 ==>k=-7 ans...